Development and Validation of a Community-Led Total Sanitation (CLTS) Evaluation Instrument for Diarrhea Intervention - Zaenal Abidin; Adelia Kusuma Prasetyo Putri (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Community-Led Total Sanitation (CLTS) is a crucial methodology for preventing diarrheal diseases; however, the availability of valid and reliable assessment tools remains inadequate. The study aims to develop and evaluate the validity and reliability of an instrument for assessing CLTS initiatives. This study employed a mixed-methods framework consisting of two distinct phases: (1) expert validation conducted by five environmental health specialists to assess content validity (Content Validity Index/CVI), and (2) reliability assessment involving 30 participants using Cronbach’s Alpha. Top of Form The content validity (Scale-Level CVI/S-CVI) for all constructs reached the threshold of ≥0.85, although two items were considered invalid (I-CVI <0.78). The reliability coefficients derived from Cronbach’s Alpha ranged from 0.61 to 0.79, with three items identified as inconsistent. Top of Form This instrument is suitable for implementation following the revision of items exhibiting ambiguity. The practical implications highlight the need for enhanced precision in monitoring CLTS programs.